Pemanfaatan Teknologi Informasi Dalam Mendorong Iklim Sekolah Positif Melalui Program Pencegahan Bullying - Munakhiroh El Hajar; Winda Nindya Putri; Siskha Putri Sayekti (Indonesian Journal Publisher, 2024)
Currently, there is an increase in bullying cases in secondary school environments such as junior high and high school, which can lead to negative impacts such as physical and mental disturbances for the victims. Bullying is an act of intimidation carried out by the stronger party against the weaker party, manifested in various forms of intimidating behavior. The purpose of the Community Service Program (PKM) at KKN is to provide education and socialization about the dangers of bullying, using technology such as videos depicting the negative impacts of bullying. In its implementation, PKM KKN uses the Participatory Action Research (PAR) method, which is a participatory method among citizens or communication through sharing approaches (the story-sharing method), in-depth interviews, and focused group discussions (FGD). The selection of this method is based on the understanding that socialization about bullying prevention involves identifying problems and implementing solutions directly related to action. The results of this counseling activity show: 1) Students can identify types of bullying, including: a) cyberbullying, b) verbal bullying, and c) physical bullying; 2) introduce anti-bullying campaigns to students; 3) create an environment that supports the development of students' personalities and social skills; and 3) encourage open communication between schools, teachers, and parents regarding the development of students' personalities and social skills.